Transformational Leadership to Improve Teacher Performance in Vocational Education: A Systematic Review - Mu'imamah, Rosita Selvina Putri; Setiadi, Bayu Rahmat (Journal of Education Method and Learning Strategy, 2026)
Transformational leadership is seen as a strategic approach to enhancing teacher performance, particularly in vocational education settings that require adaptation to industrial changes and learning innovations. This study aims to synthesize empirical findings from 30 scientific journals published between 2019 and 2024, to analyze the contribution of the four dimensions of transformational leadership of ideal influence, inspirational motivation, intellectual stimulation, and individual considerations on motivation, self-efficacy, and Performance of vocational teachers. The systematic review adheres to the PRISMA 2020 guidelines and uses data sources from ERIC, Scopus, and DOAJ. The results indicate that vocational school principals who use transformational leadership may foster a collaborative work environment, encourage pedagogical experimentation, and enhance teachers' professional engagement. Contextual factors, such as institutional support, organizational culture, and national vocational education policies, moderate the effectiveness of these leadership practices. Therefore, leadership training for vocational school principals should be designed contextually and continuously. This review provides an empirical foundation for the development of leadership-based teacher quality enhancement policies within the Technical and Vocational Education and Training (TVET) system.